Andy Gamlin interviewed by Rob Willis and Olya Willis for Voices of the bush oral history project. - Gamlin, Andrew, 1945-; Willis, Rob, 1944-; Willis, Olya. (2014)
Folkloric recording.
Recorded on 13 May 2014 in Franklin, Tasmania.
Timed summary (3 pages)
Keywords: Gamlin, Andrew, -- 1945- -- Interviews; Wooden Boat Centre (Firm); Boatbuilders -- Tasmania -- Interviews; Businessmen -- Tamania -- Interviews; Boatbuilding -- Tasmania; Wooden boats -- Tasmania; Business professionals